Tumor Necrosis Factor-α Causes Accumulation of a Ubiquitinated Form of Hypoxia Inducible Factor-1α through a Nuclear Factor-κB-Dependent Pathway - Zhou, Jie (The American Society for Cell Biology, 2003)
Hypoxia-inducible factor-1 (HIF-1) is a regulator of metabolic adaptation to hypoxia. It is now appreciated that HIF-1α accumulation is achieved under normoxic conditions by various factors, such as TNF-α. Here, it was our intention to gain insight into the signaling mechanisms used by TNF-α to stimulate HIF-1α. In tubular LLC-PK(1) or human embryonic kidney cells, TNF-α induced accumulation of HIF-1α protein but not HIF-1α mRNA. Blocking nuclear factor (NF)-κB with sulfasalazine or expression of an IκB superrepressor attenuated HIF-1α accumulation, whereas transfection of active p50/p65-NF-κB subunits mimicked a TNF-α response. Experiments with actinomycin D and cycloheximide also pointed to a transcriptional and translational process in facilitating the TNF-α response. Interestingly, and in contrast to established hypoxic signaling concepts, TNF-α elicited HIF-1α accumulation in a ubiquitinated form that still bound the von Hippel-Lindau (pVHL) protein. These data indicate that HIF-1α accumulation by TNF-α demands the NF-κB pathway, preserves ubiquitination of HIF-1α, and allows the HIF-1α-pVHL interaction.